Study of association between C-reactive protein and albuminuria in type 2 diabetes mellitus - Rastogi, Abhishek; Kumar, Ajay; Rastogi, Keerti; Kapoor, Sangeeta; Mahmood, Tariq (International Journal of Research in Medical Sciences, 2023)
Background: Inflammatory markers are excessively produced by adipocytes in T2DM due to obesity-induced dysregulation of adipocytes. Inflammation is recognised by elevated level of inflammatory markers like C-reactive protein. It has been reported that patients with nephropathy and those with albuminuria have higher levels of inflammatory markers. Methods: Study design observational descriptive cross-sectional study. 150 subjects having age more than 30 years and less than 55 years diagnosed with type 2 diabetes mellitus were included. HbA1c, FPG, creatinine, urea, CRP, and albuminuria were analysed. Results: A strong and statistically significant correlation was seen between serum CRP levels and albuminuria levels with a p value of 0.831 and a p value of 0.00. The study group was divided into two groups with normal CRP (n=40) and elevated CRP (n=110). Average values of all parameters showed a statistically significant increase in the group with abnormal CRP levels. In the ROC analysis, an area of .957 under the curve shows a very high predictive value of 15.5 mg/l of CRP for predicting albuminuria in patients of T2DM. Conclusions: From our results, we have been able to establish a strong association as well as a predictive relationship between the level of CRP and albuminuria in T2DM. We have shown that serum CRP levels at a cut-off of 15.5 mg/l are a predictor of clinically significant albuminuria. This makes serum CRP level an effective screening tool for albuminuria.